PENINGKATAN MUTU PEMBELAJARAN TAMAN PENDIDIKANALQURAN DENGAN PEMBUATAN KURIKULUM TPA - Unggul Priyadi (UII, 2013)
Seeing the many moral crisis that exists today is certainly the presence of areligious education to be one of the best solutions to save thenation's next generationof characters. As a nation with a majority Muslim population, the religious and moraleducation can begin at an early age. Religious education early childhood can be doneinformally through family and social environment, one of its forms is through TamanPendidikan Al-Qur'an (TPA). TPA as basic institutions for learning the Koran mustprovide national service and quality standards, to be able to print learners / students aresmart and professional in the field of the Qur'an so that it can address the moral crisisthat hit the country. In practice, the weakness of the landfill education in Indonesia islargely landfill does not have a standard curriculum and evaluation to assess theimplementation of the landfill. TPA in Hamlet DurenSawit, Village Selomirah, DistrictNgablak, Magelang included into the landfill that does not have a standard curriculumand evaluation to assess the implementation of the landfill. Because procurementcurriculum in the manufacture of value very important TPA curriculum should beimplemented. In addition, in order to terselengaranya conformity with the teachingcurriculum created in fact, it would require a manual containing the material listed in thecurriculum. It is also to facilitate teachers in finding teaching materials and methods ofteaching fun and enjoyable so make santriwan / wati always the spirit to go to landfill sothat the existence Wildlife Education Qur'an (TPA) more optimal and effective in thedelivery of learning materials religion Islam and can make a positive contribution,especially in the cultivation of faith and the development of faith and piety also goodmanners (akhlakul karimah).